Transformative Fiqh: Women As Witnesses To Marriage Contracts - Maswa Zayana, Nila; Waluyo Sudarmadji; Achmad Nursobah (Kartika: Jurnal Studi Keislaman, 2026)
Classical fiqh has long placed limits on women's testimony, giving preference to male witnesses based on textual interpretations of Islamic sources of law. This perspective is rooted in classical jurisprudence that considers male testimony to be superior because of the difference in rational capacity and memory between men and women. However, along with social, educational, and intellectual development, this classical approach has been increasingly criticized for being considered incompatible with the principles of justice in Islam. This study aims to analyze the concept of transformative fiqh related to the role of women as witnesses in Islamic marriage contracts. In addition, a comparative analysis was carried out on legal practices in various Muslim countries that have begun to shift to a more inclusive and competency-based witness system. This research uses a qualitative research method with a normative-juridical approach, analyzing classical fiqh texts, the principles of maqāṣid al-sharī'ah, and contemporary legal frameworks. The results of this study show that transformative fiqh offers a fairer and more relevant approach in Islamic jurisprudence, so that the testimony in the marriage contract can be in line with the principles of justice and legal certainty, without abandoning the main purpose of Islamic sharia